Estimation of time detection limit for human cytochrome b in females of Lutzomyia evansi - José Gabriel Vergara; Daniel Verbel-Vergara; Ana Milena Montesino; Alveiro Pérez-Doria; Eduar Elías Bejarano (Biomédica: revista del Instituto Nacional de Salud, 2017)
Introduction: Molecular biology techniques have allowed a better knowledge of sources of blood meals in vector insects. However, the usefulness of these techniques depends on both the quantity of ingested blood and the digestion process in the insect. Objective: To identify the time limit for detection of the human cytochrome b (Cyt b) gene in experimentally fed females of Lutzomyia evansi. Materials and methods: Eight groups of L. evansi females were fed on human blood and sacrificed at intervals of 24 hours post-ingestion. Total DNA was extracted from each female and a segment of 358 bp of Cyt b was amplified. In order to eliminate false positives, amplification products were subjected to a restriction fragment length polymorphism (RFLP) analysis. Results: The human Cyt b gene segment was detected in 86% (49/57) of the females of L. evansi, from 0 to 168 hours after blood ingestion. In 7% (4/57) of the individuals we amplified insect DNA, while in the remaining 7%, the band of interest was not amplified. We did not find any statistical differences between groups of females sacrificed at different times post-blood meal regarding the amplification of the human Cyt b gene segment or the number of samples amplified. Conclusion: The human Cyt b gene segment was detectable in L. evansi females up to 168 hours after blood ingestion.